A review on rheological properties of magnetorheological fluid for engineering components polishing. (2022) - Kumar, Manjesh; Kumar, Abhinav; Bharti, Rahul Kumar; Yadav, H.N.S.; Das, Manas
Abstract: Smart materials, by definition, are those materials whose properties change by changing an external factor such as electric current, magnetic field, capacitance etc. One such material is magnetorheological fluid. Magnetorheological fluid is a class of fluid whose apparent viscosity varies over changing magnetic flux density in the range of magnitude 1 T. Without magnetic field, magneto-theological fluid functions as a Newtonian fluid but shifts its essence to that of a non-Newtonian fluid when subjected to a magnetic field. One of the models that depict the behaviour of magnetorheological fluid is Bingham plastic fluid. Similar to Bingham plastic, magnetorheological fluid needs a certain amount of yield stress before it starts to flow, and this certain yield stress relies on the degree of the magnetic flux density applied. Magnetorheological fluids are prepared by dispersing micron-size magnetizable iron particle in a non-magnetizable solution such as deionized water, silicone oils, synthetic hydrocarbons etc. Additives such as greases are often applied to avoid sedimentation and coagulation of material. Through adding the magnetic field, the magnetizable iron particles are tied collectively in chains, along magnetic field lines, and these chain-links thicken the fluid. Conventionally magnetorheological fluids were used in rail locomotive engines, dampers, shock absorber, clutches etc. In the recent decade, magnetorheological fluids are extensively used in the manufacturing industry for finishing purposes. Certain contours, an internal section of pipes etc. are difficult to finish with other methods. Since fluid can flow within internal and hard to reach places, this can be and is manipulated. Magnetorheological fluids mixed with abrasive particles are used for such purposes. This article discusses the preparation, formulation, rheological properties and engineering applications of magnetorheological fluid in details.